Enzymes in food biotechnology : production, applications, and future prospects - Kuddus, Mohammed (Academic Press, an imprint of Elsevier, 2019)
Enzymes in Food Biotechnology: Production, Applications, and Future Prospects presents a comprehensive review of enzyme research and the potential impact of enzymes on the food sector. This valuable reference brings together novel sources and technologies regarding enzymes in food production, food processing, food preservation, food engineering and food biotechnology that are useful for researchers, professionals and students. Discussions include the process of immobilization, thermal and operational stability, increased product specificity and specific activity, enzyme engineering, implementation of high-throughput techniques, screening to relatively unexplored environments, and the development of more efficient enzymes. - Resumé vydavatel
Keywords: biotechnologie; enzymy; potravinářství; biotechnology; enzymes; food industry and trade; sborníky; papers of several authors